Maize genotype-specific exudation strategies: An adaptive mechanism to increase microbial activity in the rhizosphere. (November 2021) - Bilyera, Nataliya; Zhang, Xuechen; Duddek, Patrick; Fan, Lichao; Banfield, Callum C.; Schlüter, Steffen; Carminati, Andrea; Kaestner, Anders; Ahmed, Mutez A.; Kuzyakov, Yakov; Dippold, Michaela A.; Spielvogel, Sandra; et al.
Abstract: Plants stimulate microbial enzyme production in the rhizosphere, regulating soil organic matter decomposition and nutrient cycling. The availability of labile organic compounds (i.e. exudates) and water is the main prerequisite for such microbial activity and enzyme production, thus shaping the rhizosphere. Root morphology (i.e., root hairs) and exudate composition define the spatial distribution of properties and functions in the rhizosphere. However, the role of root architecture and exudate composition in this spatial self-organization of the rhizosphere remains unknown. We coupled three in situ imaging approaches: 14 C imaging to localize exudates, soil zymography to analyze enzyme activity distribution, and neutron radiography for water fluxes to trace the spatial structure of the rhizosphere of three maize genotypes (wild-type, mutant with defective root-hair prolongation rth3, and mutant with reduced benzoxazinoid content in root exudates bx1 ). The co-localization of these three soil images revealed the pivotal role of both optimal water content (neutron radiography) and root exudation ( 14 C imaging) for β-glucosidase production by the rhizosphere microbiome and its hydrolytic activity (zymography). Root hairs increased the exudate release and enlarged the spatial extent of increased β - glucosidase activity around the root axis by 35%, leading to a two-fold faster decomposition of 14 C exudates compared to the mutant with defective root hairs. In contrast, benzoxazinoids suppressed β - glucosidase activity by 30%, reflecting decreased microbial activity, whereas their absence broadened the rhizosphere. Overall, root hairs in wild-type maize increased microbial activity (i.e. β - glucosidase production), whereas the benzoxazinoids in root exudates suppressed microorganisms. Graphical abstract: Image 1 Highlights: Zymography, 14 C imaging, and neutron radiography were coupled to localize rhizosphere processes. Exudates are released at root tip in wild-type maize, but along the whole root in rth3 and bx1 mutants. Root hairs enlarged the spatial extent of increased β - glucosidase activity around the root by 35%. Benzoxazinoids (secondary metabolites) suppressed β - glucosidase activity in the rhizosphere by 30%. Hotspot co-localization revealed that exudates and water increased β - glucosidase activity.